KAJIAN PERLETAKAN KRIB PADA ALIRAN SUNGAI KRUENG ACEH - Muhammad Sahriat Tanjung; Eldina Fatimah; Masimin Masimin (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: The riverbank damage (erosion) which iscaused by the river scouring in Krueng Aceh River Section in Lamsie Village is dominated by behavior changes of the river due to flood discharge and flow direction.A river geometric changes process is accelerated and enhanced by the human activities which are carried out continuously such as the sand and stone mining in the river zone unpermitted. From the investigation carried out in the review location, it is found that the riverbank protection has ever been constructed by using gabion construction along the riverbank eroded, but the construction cannot restrain river water scouring so that the construction has been collapsed. To prevent the continuing erosion, the other alternative chosen is by constructing the groynes. The groynes are constructed to deflect the river current toward in turn, so that the erosion effect of the riverbank in the out turn can be reduced. This Study aims to obtain the flow pattern and flow velocity in the existing condition and the conditions of 3 (three) scenarios of groynes location in 2 (two) review locations, the first scenario mentioned that the groynes position is perpendicular to the river flow, the second mentioned that the groynes position is leaning to the upstream and the third one mentioned that the groynes position is leaning to the downstream. This study is carried out by identifying existing river condition first and then analyzed the modeling simulation using software of Surface Modeling System (SMS) running RMA2. The lengths are between 8 – 10 meter with the interval of each groynes is 15 meter. The flood discharge used in the simulation is 5 years which is 1067.00 m³/second. The result of the modeling simulation of the groynes location position found is the position which is perpendicular to the river flow (00 – 50)or scenario 1st (first) and it becomes the most effective position. This result is expected can be used as the reference for the policy maker in making the decisions in protecting the riverbank protection and controlling the water destructive power in the watershed.Keywords : Groynes, Flow Pattern, Flow Velocity, Flow DirectionAbstrak: Kerusakan tebing (Erosi) yang terjadi disebabkan oleh gerusan pada pias sungai Krueng Aceh di desa Lamsie karena didominasi oleh perubahan perilaku sungai akibat debit banjir dan arah aliran. Proses perubahan geometri suatu sungai ini menjadi dipercepat atau diperparah oleh kegiatan manusia yang secara terus menerus melakukan aktifitas penambangan pasir serta batu di zona sungai yang tidak dibenarkan. Dari investigasi di lokasi tinjauan upaya perlindungan tebing menggunakan konstruksi bronjong sudah pernah dibangun disepanjang tebing sungai yang tererosi, namun bangunan tersebut belum mampu menahan gerusan air sungai, sehingga konstruksinya kini runtuh. Untuk mencegah terjadinya erosi yang berkelanjutan, alternatif lain adalah membuat bangunan krib. Perletakan konstruksi krib dilakukan untuk membelokkan arus sungai ke arah belokan dalam, sehingga efek erosi tebing dibelokan luar dapat tereduksi. Penelitian bertujuan untuk mengetahui bentuk pola aliran dan kecepatan aliran pada kondisi existing dan 3 (tiga) skenario perletakan konstruksi krib pada 2 (dua) lokasi tinjauan, skenario pertama posisi krib tegak lurus aliran, skenario kedua krib condong ke hulu dan skenario ketiga krib condong ke hilir. Kajian ini dilakukan dengan mengidentifikasi kondisi sungai eksisting kemudian dianalisis secara simulasi pemodelan menggunakan software Surface Modeling System (SMS) running RMA2. Panjang konstuksi krib antara (8 – 10 meter) dengan jarak antara (interval) krib per (15 meter). Debit banjir 5 tahunan digunakan dalam simulasi, yang besarnya adalah 1067.00 m³/detik. Hasil simulasi menunjukan posisi perletakan konstruksi krib tegak lurus terhadap aliran (00 – 50) atau skenario 1 (satu) memberikan hasil yang efektif untuk diterapkan. Hasil ini diharapkan dapat menjadi acuan dalam rangka membuat kebijakan tentang pelaksanaan pengamanan tebing dan pengendalian daya rusak air di daerah Lamsie.